2001
DOI: 10.1523/jneurosci.21-23-09112.2001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cortical and Striatal Neurons Predict Behavioral and Electrophysiological Abnormalities in a Transgenic Murine Model of Huntington's Disease

Abstract: Neurons in Huntington's disease exhibit selective morphological and subcellular alterations in the striatum and cortex. The link between these neuronal changes and behavioral abnormalities is unclear. We investigated relationships between essential neuronal changes that predict motor impairment and possible involvement of the corticostriatal pathway in developing behavioral phenotypes. We therefore generated heterozygote mice expressing the N-terminal one-third of huntingtin with normal (CT18) or expanded (HD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
155
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(173 citation statements)
references
References 50 publications
15
155
1
Order By: Relevance
“…An involvement of HIP1 in the pathogenesis of HD is consistent with the observation that mutant htt impairs neurotransmission in mouse models of HD (Usdin et al, 1999;Li et al, 2000;Laforet et al, 2001;Zeron et al, 2002;Vetter et al, 2003). Mutant htt has been shown to directly interact with the cellular machinery required for synaptic transmission and neuronal function including PACSIN 1/syndapin, syntaxin, endophilin A, and N type channels (Sittler et al, 1998;Modregger et al, 2002;Singaraja et al, 2002;Swayne et al, 2005).…”
supporting
confidence: 82%
“…An involvement of HIP1 in the pathogenesis of HD is consistent with the observation that mutant htt impairs neurotransmission in mouse models of HD (Usdin et al, 1999;Li et al, 2000;Laforet et al, 2001;Zeron et al, 2002;Vetter et al, 2003). Mutant htt has been shown to directly interact with the cellular machinery required for synaptic transmission and neuronal function including PACSIN 1/syndapin, syntaxin, endophilin A, and N type channels (Sittler et al, 1998;Modregger et al, 2002;Singaraja et al, 2002;Swayne et al, 2005).…”
supporting
confidence: 82%
“…Synaptic abnormalities have also been reported by others in hippocampal and striatal slice preparations from HD mice (Hodgson et al, 1999;Levine et al, 1999;Usdin et al, 1999;Cepeda et al, 2001Cepeda et al, , 2003Klapstein et al, 2001;Laforet et al, 2001). Some researchers (Hodgson et al, 1999;Usdin et al, 1999) have reported deficits in posttetanic potentiation (PTP) and paired-pulse facilitation, which are indicators of calciumdependent presynaptic mechanisms.…”
Section: Discussionmentioning
confidence: 71%
“…Anomalies in the NMDA-evoked current amplitude have been observed in transgenic mice for the mutated full-length Htt, further substantiating the "excitotoxic" hypothesis (7,8). In addition, the striatum in these HD transgenic mice exhibits increased vulnerability to the toxicity of quinolinate (8).…”
mentioning
confidence: 71%